Culture of Rat Primary Cortical Cells for Microelectrode Array (MEA) Recordings to Screen for Acute and Developmental Neurotoxicity. Issue 6 (21st June 2021) - Gerber, Lora‐Sophie; van Melis, Lennart V.J.; van Kleef, Regina G.D.M.; de Groot, Aart; Westerink, Remco H.S.
Abstract: Neurotoxicity testing of chemicals, drug candidates, and environmental pollutants still relies on extensive in vivo studies that are very costly, time‐consuming, and ethically debated due to the large number of animals typically used. Currently, rat primary cortical cultures are widely used for in vitro neurotoxicity studies, as they closely resemble the in vitro brain with respect to the diversity of cell types, their physiological functions, and the pathological processes that they undergo. Common in vitro assays for neurotoxicity screening often focus on very target‐specific endpoints such as morphological, biochemical, or electrophysiological changes, and such narrow focus can hamper translation and interpretation. Microelectrode array (MEA) recordings provide a non‐invasive platform for extracellular recording of electrical activity of cultured neuronal cells, thereby enabling the evaluation of changes in neuronal (network) function as a sensitive and integrated endpoint for neurotoxicity screening. Here, we describe an in vitro approach for assessing changes in neuronal network function as a measure for neurotoxicity, using rat primary cortical cultures grown on MEAs. We provide a detailed protocol for the culture of rat primary cortical cells, and describe several experimental procedures to address acute, subchronic, and chronic exposure scenarios. We additionally describe the steps for processing and analyzing MEA and cell viability data. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Isolation and culture of rat primary cortical cells on 48‐well MEA plates Support Protocol 1 : Pretreatment and washing of 48‐well MEA plates before first use or for re‐use Support Protocol 2 : Coating of 48‐well MEA plates with 0.1% PEI solution Basic Protocol 2 : MEA measurements during acute exposure Alternate Protocol 1 : MEA measurements during subchronic exposure Alternate Protocol 2 : MEA measurements during chronic exposure Support Protocol 3 : Determination of cell viability after MEA experiments Basic Protocol 3 : MEA data processing Basic Protocol 4 : Analyzing MEA experiments after acute and subchronic exposure Alternate Protocol 3 : Analyzing MEA experiments after chronic exposure